Anti-inflammatory and wound healing potential of Alternanthera sessilis (L.) R.Br. ex DC.’s stem extract using in vitro approach - Muniandy, Katyakyini (2018)
Impaired wound healing, especially among the diabetic patients has become a major health problem and it is even more frightening with the tremendous increase in the prevalence of diabetic population worldwide. Factors such as the generation of a high amount of oxidative stress and prolonged inflammation than usual results in the delay of the healing process, therefore these factors need to be amended for an effective healing process. Currently, there are many treatments to overcome the wound healing problem, but unfortunately, most of them have some drawbacks such as the development of allergic reactions and high cost of treatment. Therefore, it was an idea to venture into natural product based treatments to enhance the healing rate. In the study conducted, Alternanthera sessilis, which was an edible functional food that is abundantly found in tropical countries, was chosen as the candidate to evaluate for its anti-inflammatory mechanism and wound healing activity on keratinocytes and normal fibroblast as well as diabetic human dermal fibroblast. The present study assessed the prepared ethanolic crude extract of stem part of A. sessilis. For the antiinflammatory properties, lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages was used as the best in vitro model. As the key inflammatory parameters, including the production of nitric oxide (NO), the cytokines such prostaglandin E2 (PGE2), interleukin (IL)-6, interleukin (IL)-1β and tumor necrosis factor (TNF)-α as well as the mediators such as cyclooxygenase (COX-2) and inducible nitric oxide synthase (iNOS) were evaluated via Griess reagent, Enzyme-Linked Immunosorbent Assay (ELISA) and Western Blot respectively. The effect of the extract on the activity of Nuclear factor-kappa-B (NF-κB) pathway using immunofluorescence and western blot techniques were examined. Subsequently, the wound healing activity involved the evaluation of cell migration on keratinocytes and fibroblast (normal and diabetic) using a scratch assay and the antioxidant activity was estimated using DPPH scavenging assay. Moreover, hyphenated techniques, Gas chromatography-mass spectrometry (GC-MS) and Liquid chromatography-mass spectrometry (LC-MS) were used for the identification of the biochemical components present in the extract. From the conducted study, it is proven that crude extract of stem of A. sessilis supports wound healing process by exhibiting anti-inflammatory properties by suppressing proinflammatory parameters via the NF-κB pathway in a dose-dependent manner.